Sex differences in mental rotation: Cortical functional connectivity using direct transfer function. (February 2018) - Sharma, Greeshma; Anto, Anson; Singh, Vijander
Highlights: Mental rotation process consists of various stages and earlier stages determine causes of sex differences in the performance. Visuospatial attention allocation network (VSAN) and mental rotation network (MRN), are explored using high density EEG by applying direct transfer function (DTF) . Earlier network changes demonstrated different activity in men and women.Men perform betterunder tough trials by using bottom-up strategy. Men perform better under tough trials by using bottom-up strategy with the advantage of spatial working memory. Men perform better due to use of a bottom-up strategy, in addition to spatial working memory. Abstract: Previous studies have reported that sex differences exist in mental rotation (MR) through different activated cortical regions, but it remains unclear what could be possible reasons of such differences in the different processing stages of MR. A few Event related potential (ERP) studies have noticed that sex differences occur in relatively early cognitive processing stages, but none of the study has viewed directional flow of information in the earlier stages as a function of complexity in men and women. This study investigated possible reasons for sex differences in visuospatial performance by flux of information underlying cortical functional connectivity. In the present study, earlier two stages were identified as a) perceptual encoding, identification, and discrimination of objects, kept under visuospatial attention allocation network (VSAN) and b) rotation ability involving spatial transformation strategy, assigned in mental rotation network (MRN). Participants underwent 3D mental rotation task with varying difficulty levels, simultaneously having electroencephalogram (EEG). It has been confirmed in behavioural outcome, as angular disparity increases, reaction and accuracy trades off. There were different activated electrodes in male and female participants for both networks. Advantage of spatial working memory was evident in men and reflected during performance. Also, VSAN showed that men utilised bottom-up attentional processes for more rotated views. MRN exhibited hemispheric lateralisation in the parietal cortex; men showed higher activation in right parietal cortex. This research work offers promising perspective to the study of cortical functional connectivity, in the terms of strength and direction, during sub-processes of MR.